The recession generation? Age-period-cohort dynamics of political trust in six countries severely affected by the 2008 crisis - Valgarðsson, Viktor Orri (Frontiers in Political Science, 2024)
A potential puzzle has emerged in the study of political trust: recent studies indicate that individuals' trust judgements are remarkably stable over their life course, but many other studies have observed long-term declines of trust in the aggregate. In particular, trust clearly declined substantially during and following the 2008 economic (and political) crisis in many European countries severely affected by it: especially Greece, Iceland, Ireland, Italy, Portugal and Spain. In this study, I focus on these countries and ask to what extent the crisis may have resulted in a “recession generation” of citizens who were in their formative years at the time and may have adopted less trusting political orientations that have persisted since, more or less independent of life-cycle and period effects. To answer this question, I present descriptive visualizations of trust levels by citizens' age over time and conduct statistical age-period-cohort (APC) analysis of political trust levels using generalized additive models (GAMs) on data from the Eurobarometer (1997–2022) and the European Values Study/World Values Survey (EVS/WVS). The findings are inconclusive: descriptive comparisons of age-by-year diagonals suggest this cohort of citizens may indeed have lower levels of trust than older and younger cohorts, above and beyond the effects of life cycle and period—but the results from GAMs differ between countries and data sources and only show the expected cohort effect in three cases. These tentative results have implications for our understanding of the nature of political trust judgements and the potential socializing effects of major political events on citizens attitude-formation, but they await confirmation in future studies which will have the benefit of longer-term data and potentially further innovations in APC analysis.